The challenge of sustaining critique across time and texts: “I never said that” about The Hunger Games - Lane, Laura; Taber, Nancy; Woloshyn, Vera (Atlantis, 2015)
This article analyzes how a group of preadolescent girls responded to the novel and film, The Hunger Games (2008; 2012) as explored throughout a series of discussion group sessions. While providing more nuanced interpretations of gender as represented in the novel, the girls were more accepting of normalized heteronormative gender performances in the film adaptation. We argue that these texts simultaneously challenge and reproduce dominant gendered and heteronormative ideas and for the importance of providing all learners with spaces for critical discussion of popular culture texts.